2017
DOI: 10.1080/09273948.2017.1327605
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Profiles of Inflammatory Cytokines in the Aqueous Humor of Glaucomatous Eyes

Abstract: The detection rates and levels of various cytokines had different patterns in POAG and NVG patients, suggesting distinctive alterations in the microenvironment in different types of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 48 publications
5
50
0
3
Order By: Relevance
“…10,11,18 However, in line with studies performed by others, 10,19 our results did not show any statistically significant difference in terms of AH Aβ 42 concentration between the glaucoma and control groups or with respect to other clinical parameters. Conversely, we found a significant increase of TP in the AH of glaucomatous patients, consistent with previous reports showing an increment of proinflammatory cytokine [20][21][22][23] and proteins related to the extracellular matrix remodeling 24 in the AH of subjects affected by glaucoma. Interestingly, our results indicate that this increase in TP was greater within the female group of glaucomatous patients, although the lower number of male patients could have biased these results (12 male vs. 20 female glaucomatous AH samples).…”
Section: Discussionsupporting
confidence: 92%
“…10,11,18 However, in line with studies performed by others, 10,19 our results did not show any statistically significant difference in terms of AH Aβ 42 concentration between the glaucoma and control groups or with respect to other clinical parameters. Conversely, we found a significant increase of TP in the AH of glaucomatous patients, consistent with previous reports showing an increment of proinflammatory cytokine [20][21][22][23] and proteins related to the extracellular matrix remodeling 24 in the AH of subjects affected by glaucoma. Interestingly, our results indicate that this increase in TP was greater within the female group of glaucomatous patients, although the lower number of male patients could have biased these results (12 male vs. 20 female glaucomatous AH samples).…”
Section: Discussionsupporting
confidence: 92%
“…; Kokubun et al. ) As a consequence of this correlation, all of our results are adjusted for the age of patients. However, systematic corrections for age have not been performed in previous studies, which may have affected the interpretation of these findings.…”
Section: Discussionmentioning
confidence: 97%
“…; Kokubun et al. ) IL‐8 is a main chemoattractant for neutrophils which have been found to accumulate in the trabecular meshwork in POAG. (Taurone et al.…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1(CCL2), MIP-1α (CCL3), and MIP-1β (CCL4) act as typical chemoattractant that is involved in the inflammatory reaction by recruiting different immune cells to the injured area (41,42). Additionally, they were previously reported to be increased in many pathological conditions of ocular inflammation, including glaucoma (43) and polypoidal choroidal vasculopathy (PCV) (44). Interestingly, in the present study, we found decreased MCP-1, MIP-1α, and MIP-1β concentrations in the eyes of SG patients when compared with the cataract eyes, indicating a conceivable 'atypical inflammation' in the aqueous humor during the disease progression.…”
Section: Iop Intraocular Pressure; C/d Cup-to-disc Ratio; the Corrementioning
confidence: 99%